Students perceptions about attention to diversity in Secondary Education Teachers Initial Training - Colmenero Ruiz, Mª Jesús; Pantoja Vallejo, Antonio; Pegalajar Palomino, María del Carmen (Revista Complutense de Educación, 2014)
This work aims to analyze the perceptions of students enrolled in the Master's Degree in Secondary Education Teaching, Training and Language Teaching at the University of Jaen, about the initial training received on attention to diversity. A descriptive methodology has been followed using an ad hoc questionnaire as data collection instrument. The results show favorable attitudes of future secondary teachers for diversity, having received an adequate training in curricular and organizational aspects, making it able to fully achieve inclusion of students with special educational needs in the classroom.
Keywords: initial training; teaching; attention to diversity; perceptions; secondary education.